Ushering in Antifungal Stewardship: Perspectives of the Hematology Multidisciplinary Team Navigating Competing Demands, Constraints, and Uncertainty. (21st May 2020) - Ananda-Rajah, Michelle R; Fitchett, Samuel; Ayton, Darshini; Peleg, Anton Y; Fleming, Shaun; Watson, Eliza; Cairns, Kelly; Peel, Trisha
Abstract: Background: The social, contextual, and behavioral determinants that influence care in patients at risk for invasive fungal diseases (IFD) are poorly understood. This knowledge gap is a barrier to the implementation of emerging antifungal stewardship (AFS) programs. We aimed to understand the barriers and enablers to AFS, opportunities for improvement, and perspectives of AFS for hematology patients at a major medical center in Australia. Methods: Semistructured, face-to-face interviews were conducted with 35 clinicians from 6 specialties (hematology, infectious diseases, pharmacy, nursing, radiology, respiratory), followed by thematic analysis mapped to a behavioral change framework. Results: Access to fungal diagnostics including bronchoscopy was identified as the key barrier to rational prescribing. Collective decision making was the norm, aided by an embedded stewardship model with on-demand access to infectious diseases expertise. Poor self-efficacy/knowledge among prescribers was actually an enabler of AFS, because clinicians willingly deferred to infectious diseases for advice. A growing outpatient population characterized by frequent care transitions was seen as an opportunity for AFS but neglected by an inpatient focused model, as was keeping pace with emerging fungal risks. Ad hoc surveillance, audit, and feedback practices frustrated population-level quality improvement for all actors. Antifungal stewardship was perceived as a specialized area that should be integrated within antimicrobial stewardship but aligned with the cultural expectations of hematologists. Conclusions: Antifungal stewardship is multifaceted, with fungal diagnostics a critical gap and outpatients a neglected area. Formal surveillance, audit, and feedback mechanisms are essential for population-level quality improvement. Resourcing is the next challenge because complex immunocompromised patients require personalized attention and audit of clinical outcomes including IFD is difficult.